2000
DOI: 10.1046/j.1365-3156.2000.00558.x
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to pay for the retreatment of mosquito nets with insecticide in four communities of south‐eastern Nigeria

Abstract: Summaryobjectives To determine the willingness to pay (WTP) for the retreatment of insecticide-treated nets (ITN) in four malaria holoendemic communities of Nigeria.methods Contingent valuation method. The study tool was a pretested interviewer-administered questionnaire. Randomly selected households were the study units and household heads or their representatives were interviewed by locally trained interviewers.results Most households were willing to pay for annual ITN retreatment in all four communities. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…The suggestion by some respondents for NHIS to cover the cost of EVV may not be an ideal option, in a country like Nigeria, where NHIS currently covers only employees in the Federal formal sector which accounts for less than 5% of the population [46]. In Nigeria, WTP studies have been conducted for several healthcare products and services [4749]. However, we are not aware of any WTP study in both Nigeria and beyond with respect to pre-vaccine deployment for EVV.…”
Section: Discussionmentioning
confidence: 99%
“…The suggestion by some respondents for NHIS to cover the cost of EVV may not be an ideal option, in a country like Nigeria, where NHIS currently covers only employees in the Federal formal sector which accounts for less than 5% of the population [46]. In Nigeria, WTP studies have been conducted for several healthcare products and services [4749]. However, we are not aware of any WTP study in both Nigeria and beyond with respect to pre-vaccine deployment for EVV.…”
Section: Discussionmentioning
confidence: 99%
“…Experiences in cost recovery have, however, demonstrated that without visible and immediate improvements in quality of care, user fees implementation will cause service utilization to drop (Alderman and Lavy, 1996;Mariko, 2003). Planning user fees on the basis of patients' preferences for improving the quality of delivered care should therefore be considered as the most appropriate way to reconcile increased efficiency and better access to health services (Asenso-Okyere et al, 1997;Onwujekwe et al, 1998Onwujekwe et al, , 2000Kadir et al, 2000;Forsythe et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The costs of buying and retreating ITNs with insecticide are major obstacles preventing their appropriate use in the community, especially in poor areas (Onwujekwe et al, 2000). However, this also provides an opportunity for neighbors to work together to obtain and use insecticide according to an appropriate schedule.…”
Section: Quantitative Evaluationmentioning
confidence: 99%